2017
DOI: 10.1038/s41598-017-01126-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Approaches Including Predictive Metagenomic Profiling Reveal Characteristics of Bacterial Response to Petroleum Hydrocarbon Contamination in Diverse Environments

Abstract: Microbial remediation of oil polluted habitats remains one of the foremost methods for restoration of petroleum hydrocarbon contaminated environments. The development of effective bioremediation strategies however, require an extensive understanding of the resident microbiome of these habitats. Recent developments such as high-throughput sequencing has greatly facilitated the advancement of microbial ecological studies in oil polluted habitats. However, effective interpretation of biological characteristics fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 81 publications
2
65
0
Order By: Relevance
“…In turn, de Menezes et al (2012) demonstrated an increased number of dioxygenase-associated transcripts belonging to Mycobacterium while investigating soil bacterial community responses to pollution with phenanthrene. Mukherjee et al (2017) showed the presence of both n-alkane and aromatic hydrocarbon utilization genes of Mycobacterium in the soil samples collected from Chinese refineries. They suggested that bacteria of this genus were among the most important hydrocarbon degraders in the tested soils.…”
Section: Bacteria Exhibiting Enhanced Hydrocarbon Degrading Potentialmentioning
confidence: 98%
See 1 more Smart Citation
“…In turn, de Menezes et al (2012) demonstrated an increased number of dioxygenase-associated transcripts belonging to Mycobacterium while investigating soil bacterial community responses to pollution with phenanthrene. Mukherjee et al (2017) showed the presence of both n-alkane and aromatic hydrocarbon utilization genes of Mycobacterium in the soil samples collected from Chinese refineries. They suggested that bacteria of this genus were among the most important hydrocarbon degraders in the tested soils.…”
Section: Bacteria Exhibiting Enhanced Hydrocarbon Degrading Potentialmentioning
confidence: 98%
“…To develop a successful bioremediation strategy, a detailed knowledge is required regarding the microbiome of a given habitat together with a deep understanding of bacterial ecological status. Several studies revealed the presence of the mentioned genera or occurrence of catabolic genes related to these taxa in hydrocarbon-polluted environments (Margesin et al 2003;Leys et al 2005;de Menezes et al 2012;Yergeau et al 2013;Mukherjee et al 2017). Margesin et al (2003) found that microorganisms containing hydrocarbon-degradative genotypes related to Pseudomonas proliferated following oil contamination.…”
Section: Bacteria Exhibiting Enhanced Hydrocarbon Degrading Potentialmentioning
confidence: 99%
“…Functional categories at different levels were computed with the script categorize by function.py. Functional differences within groups were explored using LEfSe and specific analysis was performed through the Galaxy server [38]. Output files from the PICRUSt analysis were collected and analyzed by R software (v3.5.1) for further statistical interrogation and graphical depictions of all predicted functional datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Disrupted ecosystems can also present shifts in particular taxa or overall biodiversity (Nogales et al, 2011;Mason et al, 2014;Mukherjee et al, 2017), opening the possibility to evaluate ecological status according to such metrics. Toward this goal, Aylagas et al (2017) developed two composite indicators: (1) a sediment quality index that included organic matter content, redox potential, and metal, PAH and PCB concentrations; and (2) a bacterial index of environmental quality adapted from the AMBI.…”
Section: Indications Of Ecosystem Stressmentioning
confidence: 99%